Examination of Viral Nervous Necrosis Virus in The Water Sample of The Tiger Grouper (Epinephelus fuscoguttatus) with Immunocytochemistry of Streptavidin Biotin - Putu Eka Sudaryatma; Artanti Tri Lestari; Yenny Trisnasari; D Lia Lidayana; Wahyu Nurlita (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Abstract One of potencies of marine waters that is developed, and starts to have the international market is grouper fish. Tiger grouper culture can not be separated from disease factors that may attack and destroy the cultivation. One of the important diseases that can cause mass mortality in fish, especially in grouper larvae and juveniles stadium is viral nervous necrosis (VNN). Examination by using immunocytochemical method of streptavidin biotin (SB) undertaken to develop early detection of VNN in order to be applied in preventing spread of the VNN disease in seeds of tiger groupers that are already distributed worldwide in Indonesia. And also, this SB methodology can also be applied to the tiger groupers without any injuring or even killing of the fish for the purpose of sampling. In the present study, the preliminary test was done to determine the infectivity level of the inoculum (VNN virus) owned by the Office of Fish Quarantine, Quality Control, and Fishery Safety Class I Denpasar, Bali. Whereas, the main test was done by collecting water sample from tiger grouper fish farming that was infected with VNN. The water sample was examined by using immunocytochemical method of SB after being confirmed by RT-PCR-positive test that was previously purified. Based on both SB and PCR tests having VNN positive results, it is concluded that the immunocytochemical method of SB could be applied as early, rapid and accurate detection of VNN in only a 24 hours post infection by using water as the sample. Keywords: VNN, water sample, streptavidin biotin, RT-PCR, tiger grouper